Performing forward-viewing endoscopy at time of pancreaticobiliary EUS and ERCP may detect additional upper gastrointestinal lesions - Thomas, Ashby; Vamadevan, Arunan S; Slattery, Eoin; Sejpal, Divyesh V; Trindade, Arvind J (Endoscopy International Open, 2016)
Background and study aims: It is unknown whether significant incidental upper gastrointestinal lesions are missed when using non-forward-viewing endoscopes without completing a forward-viewing exam in linear endoscopic ultrasound (EUS) or endoscopic retrograde cholangiopancreatography (ERCP) exams. We evaluated whether significant upper GI lesions are missed during EUS and ERCP when upper endoscopy is not performed routinely with a gastroscope.Patients and methods: A retrospective analysis was performed in which an EGD with a forward-viewing gastroscope was performed after using a non-forward-viewing endoscope (linear echoendoscope, duodenoscope, or both) during a single procedure. Upper gastrointestinal tract findings were recorded separately for each procedure. Significant lesions found with a forward-viewing gastroscope were defined as findings that led to a change in the patient’s medication regimen, additional endoscopic surveillance/interventions, or the need for other imaging studies. Results: A total of 168 patients were evaluated. In 83 patients, a linear echoendoscope was used, in 52 patients a duodenoscope was used, and in 33 patients both devices were used. Clinically significant additional lesions diagnosed with a gastroscope but missed by a non-forward-viewing endoscope were found in 30 /168 patients (18 %). EGD after linear EUS resulted in additional lesion findings in 17 /83 patients (20.5 %, χ2 = 13.385, P = 0.00025). EGD after use of a duodenoscope resulted in additional lesions findings in 10 /52 patients (19.2 %, χ2 = 9.987, P = 0.00157). EGD after the use of both a linear echoendoscope and a duodenoscope resulted in additional lesions findings in 3/33 patients (9 %, χ2 = 3.219, P = 0.07).Conclusion: Non forward-viewing endoscopes miss a significant amount of incidental upper gastrointestinal lesions during pancreaticobiliary endoscopy. Performing an EGD with a gastroscope at the time of linear EUS or ERCP can lead to increased yield of upper gastrointestinal lesions.